Kalibrasi Persamaan Thornthwaite Dan Evaporasi Panci Untuk Memprediksi Evapotranspirasi Potensial Pada Daerah Dengan Data Cuaca Terbatas - Humairo Saidah; Heri Sulistyono; Muh. Bagus Budianto (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2020)
Determination of irrigation channel dimensions is determined by the number of consumptive use values that are empirically determined by the potential evapotranspiration value (ETo). Due to the limited lysimeter measurement data, the ETo value is usually approached by an empirical method using weather data input. The recognized standard method for its reliability and can be used universally in determining ETo values is the FAO Penman-Monteith method. However, the use of this method is only possible if complete weather data is available. This study modified the simplest ETo calculation method, the Thornthwaite method and the evaporation pan method to obtain ETo values as accurate as FAO PM resulted. Callibrations are made by finding the correction number to get the best results shown by the high of correlation number and the efficiency index value. The results obtained are for the area with limited weather data condition, the Thornthwaite method both before and after calibration has better accuracy than the evaporation pan method. While the calibration carried out successfully increased the correlation number and efficiency index of both methods significantly. The results of the two calibrated methods, the Thornthwaite method provides better and satisfactory performance with a ratio between 0.86 and 0.89 and the efficiency index reaches 0.78.